2001
DOI: 10.1111/j.1574-695x.2001.tb00517.x
|View full text |Cite
|
Sign up to set email alerts
|

Epitope analyses of pneumococcal surface protein A: a combination of two monoclonal antibodies detects 94% of clinical isolates

Abstract: Immunisation of BALB/c mice with seven heat-treated Norwegian clinical isolates of Streptococcus pneumoniae of different serotypes elicited mainly monoclonal antibodies (mAbs) to pneumococcal surface protein A (PspA). It was remarkable that the fusions resulted only in a few mAbs directed against other protein antigens. Dot blot analysis with 16 mAbs using clinical isolates representing 23 different capsular types and the uncapsulated reference strain R36A showed that some of the mAbs bound to PspA epitopes ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 20 publications
1
11
0
1
Order By: Relevance
“…None of the six PspA/Rx1 reactive mAbs were dot blot positive against the recently genomic sequenced Norwegian clinical isolate TIGR4, which belongs to family 2 [33]. Epitope differences between PspA families 1 and 2 were further supported by the finding that the three PspA specific mAbs (143,F‐2; 149,B‐3; 180,C‐1) which showed positive flow cytometric reactions with strain 7/87 (TIGR4) [16] were non‐reactive with R6. We have previously reported that a combination of two PspA specific mAbs detected 94% of the examined Norwegian strains [16].…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…None of the six PspA/Rx1 reactive mAbs were dot blot positive against the recently genomic sequenced Norwegian clinical isolate TIGR4, which belongs to family 2 [33]. Epitope differences between PspA families 1 and 2 were further supported by the finding that the three PspA specific mAbs (143,F‐2; 149,B‐3; 180,C‐1) which showed positive flow cytometric reactions with strain 7/87 (TIGR4) [16] were non‐reactive with R6. We have previously reported that a combination of two PspA specific mAbs detected 94% of the examined Norwegian strains [16].…”
Section: Resultsmentioning
confidence: 89%
“…The mAbs were tested for binding to live pneumococci using flow cytometry as described previously [16]. Briefly, the bacteria were grown on horse blood agar overnight, then in Todd–Hewitt broth for the next night.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The active immunization of PspA from family 2 containing α-helical domain and proline-rich region provided significant cross protection when challenged with the strains from PspA families 1 and 2, while immunization with the α-helical domain of family 2 PspA alone was found involved in providing family specific protection (Moreno et al, 2010; Kothari et al, 2015). Using monoclonal antibodies, Kolberg et al (2001) found that individual mAb cross-reacted with 20–50% strains and in combination could recognize about 94% of the strains analyzed (Kolberg et al, 2001). With higher cross reactivity, antibodies generated against PspA held greater possibility of providing cross-protection against varied pneumococcal strains (Tart et al, 1996; Briles et al, 2000; Andre et al, 2015; Kristian et al, 2016).…”
Section: Role Of Pspa In Virulence and Immunogenicitymentioning
confidence: 99%
“…It was found that all epitopes recognized by these mAbs were surface accessible (Kolberg et al, 2001). Surprisingly, a combination of the two anti-PspA mAbs detected 94% of the 77 strains analyzed.…”
Section: Epitope Mapping Using Anti-pspa Monoclonal Antibodiesmentioning
confidence: 99%